Path Dependence and Transformation Mechanisms in Resource-Depleted Cities from a Resilience Perspective: The Case of Jiaozuo City - Huang, Ran (International Journal of Natural Resources and Environmental Studies, 2026)
Urban transformation is a critical development issue facing resource-depleted cities. Examining the mechanisms and driving factors of such transformation from a resilience perspective is of great significance for achieving high-quality development in resource-based cities. This paper constructs an urban resilience measurement index system based on four dimensions—economic, social, engineering and ecological—and employs the entropy method and Partial Least Squares (PLS) to conduct a quantitative assessment of Jiaozuo City’s urban resilience across different dimensions and phases from 2000 to 2021. The results indicate that: (1) Jiaozuo’s urban resilience underwent three phases—low resilience (2000–2007), moderate resilience (2008–2015) and high resilience (2016–2021)—with its resilience level exhibiting a ‘slow–rapid–slow’ upward trend. (2) Between 2000 and 2021, the driving factors behind Jiaozuo’s resilience evolution shifted gradually from economic resilience indicators and innovation-related indicators within social resilience to a combined drive from resilience indicators across all dimensions. Among these, factors such as the foundation of regional development, the level of openness to the outside world, innovative development, government management and the ecological environment were key drivers of Jiaozuo’s resilience evolution. Based on the identified primary drivers of resilience and applying the theory of evolutionary economic geography, this study summarises the transformation mechanisms to provide a reference for the transformation of other resource-depleted cities, thereby facilitating the cultivation of new-quality productive forces in such cities.